PENGGUNAAN GAME ONLINE OLEH MAHASISWA SEKOLAH TINGGI PASTORAL IPI MALANG PRODI PENDIDIKAN PENGAJARAN AGAMA KATOLIK - Teresia Noiman Derung (Jurnal Pelayanan Pastoral, 2021)
Online game s have grown rapidly in various circles of society. Specifically among students of the Catholic Education and Teaching Study Program (PPAK). The reality is that many students play online game s and forget their priorities as students. This data was obtained based on the author's observations. The impact or problem that occurs in the PPAK Study Program is that students often neglect and even procrastinate in doing the assignments given by the lecturers, also often do not attend lectures because they are tired of playing online game s. This study aims to describe how PPAK Study Program students manage time when playing online game s, the types of online game s played and how online game s relate to PPAK Study Program students. This type of research is descriptive qualitative with interview, observation and documentation methods. Analysis of the research using the model of Milles and Huberman. The conclusions in this study are: first; in terms of time management focus students cannot manage their time well. Second; In terms of content, online game s played by students have the same genre, namely Real-Time Strategy or war. Third; In the focus of media relations with individual students, students cannot control themselves when they play online game s, so they often neglect their duties and respons sibilities as students.